Fake silk : the lethal history of viscose rayon - Blanc, Paul D., 1951- (Ebscodelete 2020-10-19., 2016)
When a new technology makes people ill, how high does the body count have to be before protectives steps are taken? This disturbing book tells a dark story of hazardous manufacturing, poisonous materials, environmental abuses, political machinations, and economics trumping safety concerns. It explores the century-long history of "fake silk," or cellulose viscose, used to produce such products as rayon textiles and tires, cellophane, and everyday kitchen sponges. Paul Blanc uncovers the grim history of a product that crippled and even served a death sentence to many industry workers while also releasing toxic carbon disulfide into the environment. Viscose, an innovative and lucrative product first introduced in the early twentieth century, quickly became a multinational corporate enterprise. Blanc investigates industry practices from the beginning through two highly profitable world wars, the midcentury export of hazardous manufacturing to developing countries, and the current "greenwashing" of viscose as an eco-friendly product. Deeply researched and boldly presented, this book brings to light an industrial hazard whose egregious history ranks with those of asbestos, lead, and mercury